What drives the development of intellectual capital? A longitudinal study - Kianto, Aino; Vanhala, Mika; Ritala, Paavo; Hussinki, Henri (Routledge, 2020)
The beneficial consequences that intellectual capital exerts on various aspects of organizational performance have become well established facts demonstrated in a wide range of empirical studies. However, little knowledge exists on what drives the development of intellectual capital itself. To bridge this gap in the current understanding, this chapter examines the different organizational aspects that enhance or hinder the development of intangible value drivers. It is posited that two key groups of organizational factors are likely to impact the development of intellectual capital: strategic and structural. The theoretical model specifying these and their influence on the essential aspects of intellectual capital is tested with partial least squares (PLS)-based structural modelling, analysing a longitudinal dataset collected via two waves of surveys in 2013 and 2017 from 96 Finnish organizations. The chapter contributes to the literature on intellectual capital from a dynamic-temporal perspective, and helps to inform managers and policy-makers about the strategic and structural factors that influence the development of intellectual capital in organizations.
Keywords: enterprises; human capital; knowledge management; immaterial capital; capital; organisations (systems); business; social capital; development (active); leadership (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|